Verrucomicrobium spinosum essential genome and the divergence of cell division in the PVC superphylum - Valentina Henriques; David Moyano-Palazuelo; Maria Teresa Alonso-Pascual; Manuel Pazos; Damien P. Devos; Elena Rivas-Marin (iScience)
Summary: The Planctomycetota-Chlamydiota-Verrucomicrobiota superphylum comprises bacteria with divergent traits, epitomizing the vast biodiversity of non-model organisms that remains unexplored. Among its members, Planctomycetota and Chlamydiota exhibit unique adaptations, including variations in peptidoglycan structure and cell division without FtsZ. Verrucomicrobiota represents the only name-giving phylum within the PVC not extensively investigated. Here, exhaustive transposon mutagenesis combined with massive sequencing reveal the essential genome of Verrucomicrobium spinosum. The essentiality report demonstrates that the dcw cluster is essential except mraW. Additionally, peptidoglycan analysis evidences that the composition and saccular arrangement are canonical, contrarily to Planctomycetota and Chlamydiota. Targeted mutagenesis for V. spinosum was also developed, thus reinforcing its status as a model for Verrucomicrobiota. Ultimately, the evolutionary divergences of the dcw cluster in PVC, combined with the previous results, suggest that its Last Common Ancestor was a Gracilicutes-like bacterium dividing by an FtsZ-mediated binary fission with peptidoglycan, from which current phyla diverged.